ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN AKADEMIK DI SEKOLAH TINGGI MANAJEMEN INFORMATIKA & KOMPUTER INDONESIA - Ratnaningrum, Luh Putu Rara Ayu (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The best action that higher education institutions need to take is to use feedback from students to make service changes. Initial interviews conducted found symptoms of student dissatisfaction with the academic services provided by the campus, which shows that the quality of service has not been able to meet student expectations. Campus academic services have not played a maximum role. To determine and measure the quality of academic services and the gaps that occur, the Servqual Method is used. Measurements were made to 350 active students on campus. This study aims to determine the level of student satisfaction through Gap V on academic services. The variables in this study include tangible, reliability, responsiveness, assurance, and empathy. The analysis technique used in this research is the method of analyzing the level of interests and expectations of students to determine the suitability between the level of interests and expectations of students for and the implementation that has been done by the campus. The measurement results show that the academic services provided are not in accordance with student expectations, with the largest gap value between student expectations and campus performance in the empathy variable with a gap value of -1.5 and the smallest gap is in the Responsiveness variable of -0.5. This means that improvements need to be made in terms of empathy in serving students due to the large enough gap value. In the responsiveness variable, although the gap value is close to 0, it is still felt that it still does not meet student expectations